Allosteric Inhibitors of SHP2: An Updated Patent Review (2015-2020) - Wu, Jingwei; Zhang, Huan; Zhao, Guilong; Wang, Runling (Current Medicinal Chemistry, 2021)
Srchomology-2-domain-containing PTP 2 (SHP2) is a nonreceptor phosphatase encoded by the PTPN11 gene. Over expression of SHP2 is associated with various human diseases, such as Noonan syndrome, LEOPARD syndrome, and cancers. To overcome the shortcomings of existing orthosteric inhibitors, novel inhibitors targeting the allosteric site of SHP2 with high selectivity and low toxicity are under development. This paper reviews allosteric inhibitors of SHP2 published in patents from 2015 to 2020. The molecules are classified according to the chemical structure of the central core. SHP2 has long been considered as an ‘undruggable’ protein. Fortunately, a critical breakthrough was made by researchers from Novartis AG Ltd., who identified SHP099 as a highly potent, selective, soluble, and orally bioavailable SHP2 allosteric inhibitor. Currently, there are several allosteric inhibitors of SHP2 in clinical development. However, drug resistance is still a major challenge. The combination of SHP2 allosteric inhibitors and immunotherapy drugs or molecular targeted drugs is emerging as a promising therapeutic strategy against drug resistance.
Keywords: clinical trial